The Effectiveness of the Question-Based Learning Strategy and the Knowledge Circle in Enhancing Geography Achievement for Fifth Literary Grade Students and Developing Their Scientific Thinking (Journal of the College of Basic Education, 2025)
This research aims to study the strategies of question-based learning and the knowledge circle in the achievement of geography for fifth literary grade students and the development of scientific thinking. To achieve the objectives of this research, three null hypotheses were formulated, and the experimental method was used with two groups sharing similar educational characteristics. The experiment was conducted during the 2023–2024 academic year. The researcher selected a random sample of (90) students, divided into three groups: (30) students in the first experimental group, (30) in the second experimental group, and (30) in the control group. The two experimental groups shared similar characteristics. The researcher established (128) behavioral objectives and designed teaching plans accordingly. A set of questions was formulated to assess the students' knowledge, and these questions underwent thorough review by committee members and evaluators to ensure their suitability, resulting in a total of (40) specialized questions .After analyzing the collected data and utilizing associated statistical information, a final test consisting of (30) objective questions was developed. The study's results showed that the students in the two experimental groups, who were taught geography using the new methods, outperformed the control group, which studied the same material through traditional methods, in both academic achievement and scientific thinking assessments. Based on the collected data, the researcher reached several conclusions .